Determination of Visitor Preferences in Botanic Gardens 'Case of Nezahat Gokyigit Botanic Garden' - Karasah, Banu; Var, Mustafa (KASTAMONU UNIV, 2016)
Botanic gardens as important parts of urban green spaces are substantial centers where endangered plant species are protected and visitors are trained directly-indirectly, moreover they also offer many recreative opportunities. Nezahat Gokyigit Botanic Garden is choosen as a study area that offers to visitors chance to connect with natural life. In this study, questionnaire is prepared to determine visitors' intended use of botanic garden and their seasonal-spatial preferences and visual questionnaire is prepared determine to visitors' landscape preferences. Questionnaires are conducted face-to-face with total 311 people and visual questionnaires conducted with total 150 people in spring and autumn term. In addition, we were made a fractal analysis of preferred photographs by the visitors to reveal an objective assessment. Results showed that visitors mostly visited botanic garden recreational motivatioans like get away from busy city and stress (40.5%), spend a nice day out (14.1%) and also visitors' spatial preferences and landscape preferences can change according to seasons. In fractal analysis results, it has been seen that fractal dimension values of most preferred images by visitors were high too. Determine the visitors' preferences and their motivations are crucial for botanical garden managers to plan and design current and future development areas.
Keywords: Botanic gardens; User preferences; Landscape preferences; Nezahat Gokyigit Botanic Garden; GREEN-SPACES; URBAN GREEN; BENEFITS; PERCEPTION; RESIDENTS; QUALITY; CITIES; HEALTH; Forestry